The Impact of Indo-Nepalese Bilateral Trade Trends on Gross Domestic Product in Nepal - Adhikari, Padma Kumar; Ghimire, Krishna Prasad (Rupantaran: A Multidisciplinary Journal, 2025)
This research study intends to explore the impact of Indo-Nepalese trade trends on Nepal's gross domestic product (GDP) by highlighting the India-Nepal trade relationship and trends. Bilateral trade trends refer to the changes in the volume, value, and composition of goods and services exchanged between Nepal and India over time. Economic policies, market demands, and geopolitical relations between countries influence trade trends and GDP impacts. The study uses data from Nepal's National Accounts Section from 1991 to 2020, utilizing ordinary least squares (OLS) regression to estimate growth dependency and determine coefficient elasticity. The finding indicates that Nepal's growing reliance on foreign trade and increased remittances emphasize the need to analyze the impact of imports and exports on the country's economic development. This result has provided an understanding for policymakers in boosting economic growth by directing imports and exports in the right direction.